Evaluation of the adequacy and usefulness of the audiovisual materials of the College of Mass Communication Library based on user perception - Cardenas, Claire Monique A.; Apolinario, Rhea Rowena U. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
Audiovisual materials are teaching devices, teaching aids, and educational media or instructional materials. Teachers use them to support their teaching needs and students utilize them, to support their information needs.
This study was done with the objective of evaluating the adequacy and usefulness of the audiovisual materials of the College of Mass Communication Library based on user perception. This study used the survey method to gather data. Questionnaires were distributed to College of Mass Communication students enrolled this Academic Year (AY) 2011-2012 and faculty members who were handling classes. A total of eighty-nine (89) students and sixteen (16) faculty members participated in the survey. Among the important findings were: all of the respondents have used the audiovisual materials at the College of Mass Communication Library except the Alexis Tioseco Collection, and; majority of the respondents (35%) had used DVDs followed by VCDs (34.09%), such as film and production thesis. When asked about the audiovisual materials needed which are not available at the College of Mass Communication Library, the students mostly suggested DVDs or VCDs of current movies, easier-to-use list of available materials, PowerPoint presentation, foreign films, new films/documentaries, Filipino drama series, more documentary films, e-books, new clips, more television and properly working headphones, and soft copies of the material. Meanwhile, most of the faculty members answered they need the complete seasons of television programs, especially children's shows, historical documentaries of the Philippines, materials from the regions and students productions; collection of the old radio dramas (i.e., Gabi ng Lagim, etc.) and old TV programs (i.e., Oras ng Ligaya, etc.) which are precious and "extinct" collections which the college/university should have in its possession as the country's national university; many instructional/educational/AVP that are difficult to purchase because of cost; old radio and TV programs; soft copies like mp4 or AVI files; podcasts of popular programs, and; software copies of the materials. Moreover, most of the students (97.75%) stated that audiovisual materials were adequate to support their information needs, while ten (10) of the faculty members (62.5%) stated that the audiovisual materials were adequate to support their teaching needs. Lastly, the respondents affirmed that beta tapes were useful for their information needs and teaching needs. On the other hand, the respondents stated that VHS tapes were useful for them while VCDs were very useful for them. DVDs were very useful for both the students and faculty members. Majority of the students and faculty members (62.5%) stated that beta tapes were very useful for their information needs and teaching needs. When asked to rate the usefulness of the Alexis Tioseco Collection, majority of the students (69.66%) stated that it was useful for them while 81.25% of the faculty members stated the same.
It is recommended that the College of Mass Communication Library should look into ways on how to promote their audiovisual materials. The CMC Administration should also give attention to employ additional staff or technician to maintain the operation of audiovisual equipment.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines (Diliman). College of Mass Communication Library; Audio-visual materials -- Philippines -- Quezon City -- Use studies; Audio-visual materials -- Philippines -- Quezon City -- Evaluation